Change readiness: Creating understanding and capability for the knowledge acquisition process - Rusly, Fariza Hanim; Sun, Peter Yih-Tong; Corner, James L (Emerald Group Publishing Limited, 2015)
Purpose– This study aims to show how change readiness shapes the knowledge acquisition process. The study elicits change readiness factors, at the individual and firm levels, that influence the knowledge acquisition process and are based on the context of professional service firms.Design/methodology/approach – The qualitative study is grounded in interpretive philosophy and adopts a multiple-case study design. Three New Zealand Professional Service firms were analyzed for this study. Using grounded theory analysis, categories and concepts of change readiness that shape knowledge acquisition were identified.Findings– Knowledge acquisition understanding, knowledge acquisition context and individual differences, represent primary dimensions defining change readiness for the knowledge acquisition process. Finally, distinctive firm archetypes, inter-profession differences and professionals’ demography, affect the way change readiness elements shape the knowledge acquisition process in the firms studied.Research limitations/implications – The study develops a theoretical model that shows how elements of change readiness, at the individual and organizational levels, influence knowledge acquisition. The study offers several propositions that could be tested in future studies. The study involves three professional service firms; hence, interpretation of the findings is limited.Practical implications – A holistic understanding of change readiness factors that influence knowledge acquisition could mitigate failures of knowledge management processes in organizations.Originality/value – It is the first empirical study that seeks to develop a theory on how change readiness elements influence knowledge acquisitions in the organization.To offer more contextualized findings, the study is done within the professional service industry.